The Diverse Reactivity of Homopropargylic Amines as "Masked" 1C Synthons for the Aza‐Friedel–Crafts Alkylation of Indoles. Issue 4 (24th January 2018) - Chen, Hao; Ni, Min; Bao, Xiaofeng; Wang, Chan; Liu, Lingyan; Chang, Weixing; Li, Jing
Abstract : A novel type of "masked" 1C synthon was developed through the hydroamination cyclization‐protonation of homopropargylic amines to act as aza‐Friedel–Crafts alkylation reagents to react with indoles. A variety of 3‐(2‐pyrrolidinyl)indoles were generated in good to high yields. More significantly, some of the corresponding products display potential bioactivity against chlamydial infection, wherein they specifically target the mid‐stage of the chlamydial life cycle by interfering with RB replication. Abstract : A novel type of "masked" 1C synthon was developed through the hydroamination cyclization‐protonation of homopropargylic amines to act as aza‐Friedel–Crafts alkylation reagents to react with indoles. A variety of 3‐(2‐pyrrolidinyl)indoles were generated in good to high yields.